The American party battle : election campaign pamphlets, 1828-1876. - Silbey, Joel H. (Harvard University Press, 1999)
The 19th century was the heyday of furious contention between American political parties, and Joel Silbey attempts to capture the drama and substance of those battles in a representative sampling of party pamphlets.
Keywords: Political parties -- United States -- History -- 19th century.; Campaign literature -- United States -- History -- 19th century.; United States -- Politics and government -- 19th century.; Campagnes électorales -- Documentation -- États-Unis -- Histoire -- 19e siècle.; États-Unis -- Politique et gouvernement -- 19e siècle.; POLITICAL SCIENCE -- Political Process -- General.; HISTORY -- United States -- 19th Century.; Campaign literature; Political parties; Politics and government; United States; 1800-1899; History